Contextual factors influencing physicians' perception of antibiotic prescribing in primary care in Germany - a prospective observational study - Annika Queder; Christine Arnold; Michel Wensing; Regina Poß-Doering (BMC, 2022)
Abstract Background Antimicrobial resistance is a worldwide challenge for health services and systems alike. To reduce the overuse of antibiotics, multifaceted interventions are often used to achieve sustainable effects. It can be assumed that these effects are influenced by contextual factors. Embedded in the cluster randomized trial ARena (Sustainable reduction of antibiotic-induced antimicrobial resistance), the aim of this present study was to identify contextual factors associated with practitioners' perceptions of antibiotic prescribing in German primary health care. Methods In a prospective observational study, data were generated in a three-wave survey study between January 2018 and July 2019. Analysis was performed using logistic regression models. The outcome of interest was the physician perceived impact of participating in the ARena project on decision-making regarding antibiotic prescribing, the independent variables of interest included individual characteristics, intervention arm allocation, primary care network (PCN) environment and characteristics of the medical practice. Results Forty Six point eight percent (n = 126) of participants indicated to have perceived an impact on their decision-making regarding antibiotic prescribing by participating in the ARena project. Bivariate logistic regression analyses indicated that work experience (odds ratio (OR) 1.05, 95% confidence interval (CI) 1.006-1.103), PCN environment (OR 2.06, 95% CI 1.256-3.363), structural conditions (OR 1.66, 95% CI 1.161-2.371), environment of existing processes (OR 1.46, 95% CI 1.011-2.094), and externally defined general conditions (OR 1.57, 95% CI 1.035-2.378) were associated with physicians' perceived impact of participating in the ARena project on decision-making regarding antibiotic prescribing. In the multivariable logistic regression analysis, only work experience OR 1.05 (95% CI 1.001-1.104) continuously showed a significant influence. Conclusions This study indicates that contextual factors at individual, practice, and system level influence physicians' perceptions of antibiotic prescribing. Longer work experience appeared to be a significant influencing factor to be considered in antimicrobial stewardship programs. Trial registration ISRCTN, ISRCTN58150046 (registered 13.09.2017).